Factors affecting The Occurrence of Tuberculosis Destroyed Lung (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Pulmonary Tuberculosis (TB) disease remains a public health. In recent years, the prevalenceof TB has increase. Dangerous complication of Pulmonary TB can destroy lungs. In 83.3% cases ofdestroyed lung, the patient are found to have a history of pulmonary tuberculosis. Objective: The aimedof this study was to identify factors affecting the occurrence of Tuberculosis Destroyed Lung in LampungProvince, Indonesia in 2017. Method: This study is an analytic observation with a case control design. Thesample were obtained through total sampling. Primary and secondary data were obtained from interviewand medical records. The samples were taken from 64 patients in several hospitals in Lampung, Indonesia.Results: The results showed the relationship between age with destroyed lung (p = 0.897), gender withdestroyed lung (p = 0.511), education level with destroyed lung (p = 0.754), occupation with destroyed lung(p = 0.060), income with destroyed lung (p = 0.482), cigarette smoking with destroyed lung (p = 0.013),and the presence of multiple diseases with destroyed lung (p = 0.748). Conclusions: There is a significantrelationship between Cigarette Smoking to the incidence of destroyed lung.
Keywords: Tuberculosis Lung, Destroyed Lung, cigarette smoking